A Controversy About The Authority of Khabar Al-Wahid With Special Reference to Al-Shafi'i's Views - Ali, Abdul Karim (Jurnal Usuluddin, 1998)
This article attempts to elaborate the different views of different madhhabs about the authority of Khabar Al-Wahid in general, with special reference to al-Shafi'i's points of view.